Upaya Seorang Istri Membantu Perekonomian Keluarga (Experiential Learning pada Pengusaha Wanita Yang Menggunakan Medsos Lawas Facebook) (Indo-MathEdu Intellectuals Journal, 2024)
The increasing demands of life have made many housewives take creative economic steps to support their family's financial needs, especially in the condition of their husbands with limited income. One way is to open an online business through social media. This study aims to find out how experiential learning in a female entrepreneur who still uses old social media, namely Facebook, to trade her goods as a form of her efforts to help her family's economy. This research is qualitative research with a phenomenological approach. Data collection uses in-depth interviews on the subjects. Data analysis uses qualitative data analysis consisting of data reduction, data presentation, and conclusion drawn. This study found three major themes with nine sub-themes related to experiential learning. Experience before migrating with the sub-themes of independence, work spirit, and entrepreneurial spirit. Furthermore, the experience when migrating with the sub-themes of hard work, boss trust, and working while studying. Entrepreneurial experience with the background sub-theme of starting a business, starting a business, and managing a business. From the application of experiential learning, good psychological effects on the subject such as self-efficacy, resilience, and work-life balance are formed